Common fixed point results for three maps in generalized metric space - Abbas, Mujahid; Nazir, Talat; Saadati, Reza (Advances in difference equations, 2011)
Mustafa and Sims [Fixed Point Theory Appl. 2009 , Article ID 917175, 10, (2009)] generalized a concept of a metric space and proved fixed point theorems for mappings satisfying different contractive conditions. In this article, we extend and generalize the results obtained by Mustafa and Sims and prove common fixed point theorems for three maps in these spaces. It is worth mentioning that our results do not rely on continuity and commutativity of any mappings involved therein. We also introduce the notation of a generalized probabilistic metric space and obtain common fixed point theorem in the frame work of such spaces. 2000 Mathematics Subject Classification : 47H10.